STRATEGI GURU DALAM MENGHADAPI GAYA BELAJAR SISWA KELAS IV SD NEGERI KADILANGU 1 - Sayyidatul Munnah; Syafira Ashna Putri Nuha; Rani Setiawaty (Universitas Muhammadiyah Kuningan, 2024)
This research aims to determine teachers' strategies in dealing with the learning styles of class IV students at SD Negeri Kadilangu 1. This research uses a qualitative descriptive research type with an exploratory approach. The object of this research is the teacher's strategy in dealing with student learning styles. Data collection techniques in this research are observation, interviews and documentation. The data analysis technique uses the Miles and Huberman interactive analysis model which consists of data reduction, data presentation and conclusion. The data validity technique uses triangulation techniques, namely by comparing the results of interviews, observations and documentation. Based on the results of this research, it was concluded that there were 12 students with a visual learning style, 12 students with an auditory learning style and 2 students with a kinesthetic learning style. The teacher's strategy in dealing with students' differences in learning styles is to use teaching methods that are easy for students to understand so that with students' different learning styles, students can easily understand these methods. The methods used are demonstration, discussion, question and answer teaching methods and others accompanied by the use of varied media, for example teaching aids according to the context being taught and using IT.